Analysis Of The Sharia Business Model Based On The Business Model Canvas And The Marketing Strategy Of Al-Bahjah Chicken Sendang - Nono Sutrisno; Muhammad Saechu; Heru Kurniawan (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study was motivated by the growth of Sharia-based culinary businesses that integrate business objectives with Islamic values in their business practices and marketing. Al-Bahjah Chicken Sendang is a culinary business under the auspices of the Al-Bahjah Foundation that is not only focused on economic profit but also supports the Islamic missionary activities of the Islamic boarding school. This study aims to analyze the implementation of the Sharia business model and the marketing strategies applied by Al-Bahjah Chicken Sendang. The study employs a qualitative approach using field research. Data were collected through observation, in-depth interviews, and documentation involving management and business operators. Data analysis was conducted through data reduction, data presentation, and drawing conclusions using triangulation techniques to test data validity. The results indicate that Al-Bahjah Chicken Sendang’s business model has implemented Sharia business principles, reflected in business management, the application of standard operating procedures, the use of halal products, and a business orientation that prioritizes the values of blessings and da’wah. Based on the Business Model Canvas approach, this business has broad market segmentation, a value proposition based on product quality and religious values, and business partnerships that support business development. Marketing strategies are implemented through digital promotions, social media, discounts, and services based on Islamic business ethics. These strategies are effective in boosting sales and strengthening customer loyalty.